2014
DOI: 10.1136/amiajnl-2013-002230
|View full text |Cite
|
Sign up to set email alerts
|

BigMouth: a multi-institutional dental data repository

Abstract: Few oral health databases are available for research and the advancement of evidence-based dentistry. In this work we developed a centralized data repository derived from electronic health records (EHRs) at four dental schools participating in the Consortium of Oral Health Research and Informatics. A multi-stakeholder committee developed a data governance framework that encouraged data sharing while allowing control of contributed data. We adopted the i2b2 data warehousing platform and mapped data from each in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 16 publications
(15 reference statements)
0
54
0
Order By: Relevance
“…More recently, six members of COHRI, coordinated by the University of Texas Health Science Center at Houston, have collaborated to share partially de-identified electronic health record data through the 'BigMouth Dental Data Repository'. 12 Partners are able to query data across all sites to rapidly obtain anonymised data summaries, and more detailed, patient-level data with appropriate approvals. Access to these data is currently limited to partnering institutions, and information about non-oral health is limited to data available in the dental electronic health records with no direct links to patients' medical records.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, six members of COHRI, coordinated by the University of Texas Health Science Center at Houston, have collaborated to share partially de-identified electronic health record data through the 'BigMouth Dental Data Repository'. 12 Partners are able to query data across all sites to rapidly obtain anonymised data summaries, and more detailed, patient-level data with appropriate approvals. Access to these data is currently limited to partnering institutions, and information about non-oral health is limited to data available in the dental electronic health records with no direct links to patients' medical records.…”
Section: Introductionmentioning
confidence: 99%
“…Digitalization of clinical examinations and medical records -called subject metadata -is becoming a standard in health care systems and adds to the data deluge that could be analyzed. For instance, a multi-institutional dental data repository has been developed with 1.1 million patient data at the time of release in 2012 [Walji et al, 2014].…”
Section: Healthy Oral Ecosystemmentioning
confidence: 99%
“…The pooled data showed that patients had a high prevalence of caries and periodontal disease on the basis of diagnostic information, not treatment data, an important distinction because treatment data do not reflect the subset with untreated disease. 42 Through BigMouth and the use of the DDS terminology, we also have been able to quantify adherence to practice guidelines for managing chronic moderate periodontitis. 41 We readily were able to determine that a full 15% of patients with a diagnosis of chronic moderate periodontitis received only prophylaxis, which is below the standard of care set by the American Academy of Periodontology.…”
Section: Discussionmentioning
confidence: 99%